Heat-treated copper phthalocyanine on carbon toward electrochemical CO2 conversion into ethylene boosted by oxygen reduction. Issue 87 (14th October 2022) - Li, Mengyao; Li, Tiantian; Wang, Renquan; Sun, Chongyun; Zhang, Na; Gao, Rui; Song, Yujiang
Abstract : Heat-treated copper phthalocyanine on carbon demonstrates high C2 H4 selectivity at a low potential due to the in situ generated OH − . Abstract : Copper phthalocyanine on carbon (CuPc/C) after pyrolysis exhibits a C2 H4 Faradaic efficiency (FEC2 H4 ) of 42.6 ± 0.5% at an extremely low potential of −0.4 V vs. RHE toward the electrochemical CO2 reduction reaction (CO2 RR), significantly boosted by the in situ oxygen reduction reaction (ORR).